Europe's energy policy and the task ahead - Guido Brunner (Intereconomics, 1977)
The oil shock of 1973 and the subsequent world recession have drastically demonstrated the weakness of countries dependent on external energy supplies. In the following, Guido Brunner, the competent Member of the Commission of the European Communities, describes the changes we are facing in the energy field and what the Community is doing to face up to them.
Keywords: 330; Energy